2004
DOI: 10.1097/00002030-200406003-00005
|View full text |Cite
|
Sign up to set email alerts
|

Scaling-up HIV treatment programmes in resource-limited settings

Abstract: Community-based care of AIDS has been highly effective in rural Haiti. With more international financial support for HIV/AIDS treatment in resource-limited settings, there should be no barriers to access to life-saving HAART for those who need it most.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(116 citation statements)
references
References 5 publications
5
109
2
Order By: Relevance
“…In Haiti, antiretroviral treatment was successfully provided in the context of a comprehensive programme of HIV care, tuberculosis and STI prevention and treatment, together with women's health. 128 It was reported that integrated HIV prevention and care strengthened primary health care, and in particular regarding women's health, increased attendance for antenatal care. However, available quantitative evidence is limited, including in terms of the impact of integrated care on family planning.…”
Section: Family Planning In Pmtct Servicesmentioning
confidence: 99%
“…In Haiti, antiretroviral treatment was successfully provided in the context of a comprehensive programme of HIV care, tuberculosis and STI prevention and treatment, together with women's health. 128 It was reported that integrated HIV prevention and care strengthened primary health care, and in particular regarding women's health, increased attendance for antenatal care. However, available quantitative evidence is limited, including in terms of the impact of integrated care on family planning.…”
Section: Family Planning In Pmtct Servicesmentioning
confidence: 99%
“…Our predicted levels of transmitted resistance are low, because our predictions are only short term (to 2008). Relatively high levels of acquired resistance would be likely to emerge after several years on treatment (3-6); as levels of acquired resistance rise, levels of transmitted resistance will increase (16,17). For longer time periods, our model predicts higher levels of transmitted resistance.…”
Section: Resultsmentioning
confidence: 91%
“…Accompagnateurs, or community health workers, were people chosen from the local community and trained in medication and symptom management for HIV patients. Since starting this program, patients have experienced an increase in CD4 count and reduction in viral loads, and therefore the accompagnateurs have been identified as a critical component of the clinical care provided for these patients (Koenig, Leandre, and Farmer 2004;Behforouz, Farmer, and Mukherjee 2004).…”
Section: Haitimentioning
confidence: 99%